Pili Torti: A Clue to Life-threatening Illness - A Rare Case Report - Nikita M. Patel; Sanya K. Narang; Jatin D. Chauhan; Hiral A. Shah (Wolters Kluwer Medknow Publications, 2024)
Menkes kinky hair disease (MKHD) is a rare inherent error of copper metabolism presenting during early infancy with multi-system involvement. It is associated with high morbidity and mortality in early childhood. Characteristic hair changes mirror internal metabolic alterations. Here, we report a case of 13-month-old male child who presented with peculiar changes of skin and hair along with convulsion and high-grade fever. Dermatoscopy and hair mount examination showing pili torti with pigmentary dilution pointed toward the diagnosis of MKHD, which was further enforced with blood investigations showing low copper and ceruloplasmin levels. Cutaneous findings play a crucial role in early diagnosis, thereby reducing morbidity with timely treatment.